2011
DOI: 10.1371/journal.pone.0022974
|View full text |Cite
|
Sign up to set email alerts
|

The 3-Hydroxy-2-Butanone Pathway Is Required for Pectobacterium carotovorum Pathogenesis

Abstract: Pectobacterium species are necrotrophic bacterial pathogens that cause soft rot diseases in potatoes and several other crops worldwide. Gene expression data identified Pectobacterium carotovorum subsp. carotovorum budB, which encodes the α-acetolactate synthase enzyme in the 2,3-butanediol pathway, as more highly expressed in potato tubers than potato stems. This pathway is of interest because volatiles produced by the 2,3-butanediol pathway have been shown to act as plant growth promoting molecules, insect at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 76 publications
2
65
0
1
Order By: Relevance
“…This was for instance observed for Pectobacterium species, bacterial pathogens responsible for soft rot disease in potato. Disruption of the biosynthesis of the volatile Volatile affairs in microbial interactions R Schmidt et al 2,3-butanediol coincided with reduced virulence (Marquez-Villavicencio et al, 2011). Volatile compounds can also have a role in the attraction of other microorganisms.…”
Section: Volatile Affairs In Microbial Interactions R Schmidt Et Almentioning
confidence: 99%
“…This was for instance observed for Pectobacterium species, bacterial pathogens responsible for soft rot disease in potato. Disruption of the biosynthesis of the volatile Volatile affairs in microbial interactions R Schmidt et al 2,3-butanediol coincided with reduced virulence (Marquez-Villavicencio et al, 2011). Volatile compounds can also have a role in the attraction of other microorganisms.…”
Section: Volatile Affairs In Microbial Interactions R Schmidt Et Almentioning
confidence: 99%
“…Pectobacterium and Dickeya, like many bacteria, encode the butanediol pathway, which results in the production of the potent insect attractant acetoin, suggesting that these bacteria may attract insect vectors to infected plant material through this route (37,100). Once associated with an insect, some isolates of Pectobacterium carotovorum can infect and persist in D. melanogaster and activate an immune response (8,9).…”
Section: Insects As Vectors and Alternate Hostsmentioning
confidence: 99%
“…Later, Liu et al (88) showed that AHL-mediated quorum sensing regulates one quarter of Pectobacterium genes, including many virulence genes. AHL is unstable at alkaline pH (15) and SRE raise the pH of their environment during infection (100,109,118), so the role AHL plays during disease may be transient.…”
Section: Intercellular Bacterial Signal Moleculesmentioning
confidence: 99%
“…In fact, the latter bacteria follow the mixed-acid fermentation route during the early stages of growth and switch to the 2,3-butanediol route in the late-exponential phase (3,4). This switch is generally viewed as a strategy of these bacteria to prevent excessive medium acidification, and it has been demonstrated that knockout of the 2,3-butanediol pathway indeed results in more-pronounced acidification, early growth arrest, and cell death (5,6).…”
mentioning
confidence: 99%